If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -6 = 2a + -4 Reorder the terms: -6 + 4a = 2a + -4 Reorder the terms: -6 + 4a = -4 + 2a Solving -6 + 4a = -4 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -6 + 4a + -2a = -4 + 2a + -2a Combine like terms: 4a + -2a = 2a -6 + 2a = -4 + 2a + -2a Combine like terms: 2a + -2a = 0 -6 + 2a = -4 + 0 -6 + 2a = -4 Add '6' to each side of the equation. -6 + 6 + 2a = -4 + 6 Combine like terms: -6 + 6 = 0 0 + 2a = -4 + 6 2a = -4 + 6 Combine like terms: -4 + 6 = 2 2a = 2 Divide each side by '2'. a = 1 Simplifying a = 1
| 4x+2+x=-10 | | N-5*.66=.75 | | 2x+7-10=3 | | 2(x+1)+34=-4 | | 3x+(-6)=6 | | 3x+1=35 | | -5x+7(-4x+17)=-178 | | 3(a+1)=4(a-1.5) | | 50t=0.25t+1000 | | -2x+121=0 | | h=-16t^2+48t+7 | | 8+x=3Xx | | 5p+2p-3p= | | -8+5x=3+7(x-1) | | Y-4=5y | | -7=3x | | -125=5(w-12) | | 15b-14a+5b+16a= | | 6(1-6x)=-25-5x | | 3(2y+5)=11 | | 14+d-6=7 | | Y-5=-(4-y) | | 12w=16(w-8) | | -75m=15 | | a^4+2a^2-3=0 | | -49=a+5 | | 5b+12=-5 | | -(6p+8)+4p=-1-p | | 64=2x+20 | | 4+4b=1 | | -7n-33=-8(8-3n) | | ln(x+6)=9 |